Implementasi Infrastruktur TI Berbasis Virtualisasi untuk Meningkatkan Efisiensi dan Fleksibilitas Sistem Informasi di SMK Modis Tenjo - Agung Wibawa; Habib Nurfaiza; Budianto Budianto (CV. ALIM'SPUBLISHING, 2026)
The development of information technology encourages educational institutions to have IT infrastructure that is efficient, flexible, and capable of optimally supporting information system services. However, the use of separate physical servers often results in low resource utilization, high operational costs, and limitations in system management. This study aims to implement virtualization-based IT infrastructure to improve the efficiency and flexibility of the information system at SMK MODIS Tenjo. The research method used is an experiment with a quantitative approach through a pre-test and post-test design. The research stages include needs analysis, virtualization system design, VMware ESXi implementation, and migration of physical servers to virtual (Physical to Virtual/P2V), as well as testing and evaluating system performance. The research results show that the implementation of virtualisation successfully consolidated 15 physical servers into 3 host servers with several virtual machines without reducing service quality. In addition, CPU utilisation increased from 12% to 75%, operational costs decreased by up to 46%, and server deployment time was reduced from 5 days to less than 2 hours. The implementation of High Availability (HA) features also improved system reliability by reducing service recovery time from 3 days to less than 2 hours. Based on these results, virtualisation has proven effective in enhancing the efficiency, flexibility, and reliability of IT infrastructure in the educational environment.